The Classmates Social Isolation Questionnaire for Adolescents (CSIQ-A): Validation and Invariance across Immigrant Background, Gender and Socioeconomic Level - Elisa Cavicchiolo; Laura Girelli; Fabio Lucidi; Sara Manganelli; Fabio Alivernini (LED Edizioni Universitarie, 2019)
It is widely acknowledged that the social relationships of adolescents with their classmates can have a significant impact on their adjustment to the school environment and their psychological well-being. This study, based on a random sample of 36,712 students, investigates the psychometric properties and the validity of the Classmates Social Isolation Questionnaire for Adolescents (CSIQ-A), a time-efficient instrument intended to measure peer relatedness at school. Confirmatory factor analysis established the bidimensional structure of the scale. The CSIQ-A showed measurement invariance across gender and across students with different immigrant backgrounds and socioeconomic status. A positive correlation between peer acceptance, peer friendship and positive affect provided support for the criterion validity of the measure. The CSIQ-A proved to be a psychometrically sound measure, which can be reliably used with  adolescents with different sociodemographic and cultural characteristics. In conclusion, the CSIQ-A makes it possible to directly measure the effects of classroom interventions that are aimed at promoting peer relatedness and preventing social isolation.